The history of anesthesiology and intensive care unit of Neurosurgical Institute n.after acad. A.P.Romodanov, Academy of medical Sciences of Ukraine - Spasichenko, P. V.; Yarotskiy, R. Y.; Gavrish, R. V. (Ukrainian Neurosurgical Journal)
In the article short history of foundation and development of intensive care and anesthesiology department in Kiev Neurosurgical Institute is presented. Main direction of practical activity includes neuroanesthesia for diagnostic investigations and surgery, intensive care for patients with severe brain injury (adult and children), for patients, including children, with oncologic and vascular pathology of brain and spine.